Β‐Cyclodextrin‐Decorated Carbon Dots Serve as Nanocarriers for Targeted Drug Delivery and Controlled Release. Issue 4 (28th January 2019) - Yang, Ting; Huang, Jing‐Li; Wang, Yi‐Ting; Zheng, An‐Qi; Shu, Yang; Wang, Jian‐Hua
Abstract: A novel nanocarrier for targeted delivery of anti‐cancer drug doxorubicin (DOX) was fabricated with carbon dots (CDots) as the matrix. Fluorescent CDots capable of targeting folate receptor‐positive cells first conjugate with boric acid and then couple with β‐CD to produce the nanocarrier β‐CD/CDots. DOX was encapsulated into the cavity of β‐CD providing a maximum loading ratio of 27.3% at pH 7.4. Benefiting from pH‐sensitive dissociation of DOX/β‐CD inclusion complex and the cleavage of the bonding between boric acid and β‐CD, pH‐triggered release of drugs was realized, with an 82% release of the loaded drug at pH 5.0. Meanwhile, the fluorescence resonance energy transfer (FRET) occurs between CDots (donor) and DOX (acceptor), which may potentially facilitate monitoring/tracing of the drug delivery process. In vitro results further demonstrated the targeting capability of the nanocarrier towards folate receptor‐positive cells. Moreover, confocal microscopy results, in accordance with that of flow cytometry analysis, confirmed the efficient intracellular uptake of DOX‐β‐CD/CDots and sustained release of DOX. This makes DOX‐β‐CD/CDots promising as biocompatible and multifunctional nanomedicine for targeted delivery, controlled release and real time monitoring/tracing of drugs. Abstract : Dots of light : Fluorescent CDots capable of targeting folate‐receptor‐positive cells first conjugate with boric acid and then couple with β‐CD to produce the nanocarrier β‐CD/CDots. DOX was encapsulated into the cavity of β‐CD providing a maximum loading ratio of 27.3% at pH 7.4, and pH‐triggered release of drugs was realized with an 82% release of the loaded drug at pH 5.0.